2012
DOI: 10.1186/1687-9856-2012-31
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin A1c measurement for the diagnosis of Type 2 diabetes in children

Abstract: Laboratory measurements of hemoglobin A1c above 6.5% were approved as an additional diagnostic criteria for diabetes mellitus by the American Diabetes Association in 2010. Several recent pediatric studies have cast HbA1c measurement in children in an unfavorable light in the pediatric population, by comparing HbA1c measurements to results on oral glucose tolerance test (OGTT) or fasting plasma glucose (FPG). However, many of these studies do not recognize that diabetes diagnostic criteria are based upon long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 20 publications
0
37
1
Order By: Relevance
“…Recent studies question the validity of A1C in the pediatric population, especially among certain ethnicities, and suggest OGTT or FPG as more suitable diagnostic tests (33). However, many of these studies do not recognize that diabetes diagnostic criteria are based on long-term health outcomes, and validations are not currently available in the pediatric population (34). The ADA acknowledges the limited data supporting A1C for diagnosing type 2 diabetes in children and adolescents.…”
Section: Testing For Type 2 Diabetes and Prediabetes In Children Andmentioning
confidence: 99%
“…Recent studies question the validity of A1C in the pediatric population, especially among certain ethnicities, and suggest OGTT or FPG as more suitable diagnostic tests (33). However, many of these studies do not recognize that diabetes diagnostic criteria are based on long-term health outcomes, and validations are not currently available in the pediatric population (34). The ADA acknowledges the limited data supporting A1C for diagnosing type 2 diabetes in children and adolescents.…”
Section: Testing For Type 2 Diabetes and Prediabetes In Children Andmentioning
confidence: 99%
“…This paradox is one shared by previous studies, which have shown poor agreement among the ADA’s three different prediabetes criteria (18, 2123). All three measures are flawed in that they lack validation in the pediatric population (24), emphasizing the need to corroborate prediabetic measures in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies question the validity of A1C in the pediatric population, especially among certain ethnicities, and suggest OGTT or FPG as more suitable diagnostic tests (52). However, many of these studies do not recognize that diabetes diagnostic criteria are based on long-term health outcomes, and validations are not currently available in the pediatric population (53). The ADA acknowledges the limited data supporting A1C for diagnosing type 2 diabetes in children and adolescents.…”
Section: Screening and Testing For Type 2 Diabetes And Prediabetes Inmentioning
confidence: 99%